Pelatihan Dan Pendampingan Aplikasi Siapik Dalam Pencatatan Transaksi Keuangan UMKM Kayu Mulia Barokah (International Forum of Researchers and Lecturers, 2023)
This activity was carried out to provide training and assistance regarding the recording of financial transactions that exist in the Kayu Mulia Barokah UMKM. This UMKM is located in Purworejo Regency, Central Java. Recording of financial transactions carried out by UMKM Kayu Mulia Barokah is still done manually and combines the owner's personal finances and company finances, so that the owner cannot know clearly how much profit is generated. This happens because business owners do not understand the basis for recording financial transactions and the importance of financial reports. Based on these problems, training and assistance were carried out for recording financial transactions at UMKM Kayu Mulia Barokah.